Reconstruction of Pesantren Education, Analyzing Independent Curriculum in Transforming Islamic Education in Indonesia - Zainuddin Zainuddin; Aidah Aidah; Mustafiyanti Mustafiyanti; Anis Susanti (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
This study aims to analyze the reconstruction of the pesantren education system in implementing the Merdeka Curriculum as part of the transformation of Islamic education in Indonesia. Pesantren as the oldest Islamic educational institution has a strong tradition of learning the yellowclassical books through classical methods such as sorogan and bandongan. However, the dynamics of changes in the national education system require pesantren to adapt to the Merdeka Curriculum which emphasizes strengthening 21st century competencies, learning flexibility, and learner-oriented. This research uses the library research method by analyzing various relevant literature, scientific journals, books, and official documents. The results showed that the reconstruction process of the pesantren education system in adopting the Merdeka Curriculum was carried out selectively and contextually without eliminating the identity and characteristics of the pesantren. The pesantren adjusts the curriculum, learning methods, and evaluation system by integrating Islamic values and modern digital-based competencies and strengthening 21st century literacy. The role of kyai as a cultural broker is a key factor in maintaining the balance between maintaining tradition and opening space for educational innovation. However, pesantren face challenges such as limited human resources, infrastructure, and tensions between the autonomy of the pesantren curriculum and national curriculum standards. For this reason, strategies are needed to strengthen institutional capacity, improve teacher competence, and develop hybrid learning models that combine traditional and modern methods. This study concludes that the reconstruction of the pesantren education system in the Merdeka Curriculum is a strategic step to strengthen the role of pesantren as Islamic educational institutions that are adaptive, innovative, and remain rooted in Islamic values in facing the challenges of globalization and digitalization of education